The Association between Betel Quid Chewing and Metabolic Syndrome among Urban Adults in Mandalay District of Myanmar - Aung, Aye Aye; Zin, Sai Ni Soe; Ko Ko, Aung; Thet, Aung Cho (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Background. As the prevalence of metabolic syndrome, obesity and diabetes increase worldwide, the need to identify modifiable lifestyle risk factors also increases, especially those that may be relatively unique to a specific population. To explore a possible association between betel quid chewing and metabolic syndrome, a community-based cross-sectional study was conducted. Methodology. Three hundred ninety-one (391) adults were interviewed and the following parameters were measured: triglycerides, HDL-cholesterol, glucose, waist circumference, body mass index and blood pressure. Multiple logistic regression was used to determine the association between betel quid chewing and metabolic syndrome while controlling for confounders. Results. The prevalence of metabolic syndrome was similar in chewers and non-chewers, 50% and 49%, respectively. After controlling for other factors, development of metabolic syndrome was positively associated with number of betel quid chewed per day, age greater than 40 years , and a positive family history of hypertension and diabetes. Regarding the duration of betel chewing, when analyzed by sex, the risk was doubled in men compared to non-chewers (OR 2.15; 95% CI = 1.21, 3.84]). As a result, a man chewing more than 10 pieces (OR 2.49; 95% CI = 1.36, 4.57]) of betel quids per day for more than 10 years had a two-fold increased chance of developing the metabolic syndrome. Conclusions. Frequency and duration of betel quid chewing may represent a behavioral lifestyle target for approaches to reduce the incidence of metabolic syndrome.